ANALISIS SENSITIVITAS MAKRO EKONOMI TERHADAP PROFITABILITAS BANK MUAMALAT INDONESIA (IAIN Tulungagung, 2018)
Abstract: This study attempts to assess variable influence macroeconomic that is represented exchange rates, inflation and interest rates to profitability represented ROA and ROE PT. Bank muamalat Indonesia, Tbk period of 2008 until 2015. The Objects research is the bank muamalat Indonesia. An analysis of data using multiple linear regression on the SPSS 23.0 version. The research suggests that simultaneously variables macroeconomic is not affect on ROA and ROE Bank Muamalat Indonesia period of 2008 until 2015. A partial only variable inflation significant negative on ROA and ROE PT. Bank Muamalat Indonesia, Tbk while variable exchange rates and interest rates is not affect on ROA and ROE Bank Muamalat Indonesia.